The Realization Of Politeness Strategies In Verbal Disagreement By Jordanian Arabic Speakers: A Socio-Pragmatic Analysis - Alazzam, Sakher Naji Mohammad (2021)
This study aims to identify the verbal disagreement strategies that are used in Jordanian Arabic, and to determine the politeness strategies that are used for showing verbal disagreement in Jordanian Arabic. The present study also attempts to examine how gender, social status, and social distance among interlocutors affect selection of politeness strategies when showing verbal disagreement.